Macrophage and angiogenesis intensity within proliferative non neoplastic and neoplastic oral lesions - Sudiono, Janti; Howuk, Barnabas; Fransisca, Cindy (Padjadjaran Journal of Dentistry, 2018)
The most common chronic inflammation involved dental and oral tissue is gingival polyp, pulp polyp, and fibroma that are proliferative non neoplastic and neoplastic condition. Chronic inflammation will induce cells and vascular proliferation as well as biological nature lesion. Previous study revealed that increase macrophage followed by increase angiogenesis intensity. Increase angiogenesis or vascular proliferation indicates progressive growth in form of proliferative non neoplastic or neoplastic disease outside of their easily bleeding clinical features. This study evaluated macrophage and angiogenesis intensity and their correlation within such oral lesions. Samples used are of oral mucosa excision with clinical diagnose of gingival polyp (n=3); pulp polyp (n=3); and fibroma (n=3). Macrophage was detected using immunostaining with CD68 antibody resulted in brown staining cell membrane under light microscope while angiogenesis intensity evaluated as number of blood vessels. The results showed there was mild positive correlation of angiogenesis intensity and CD68+ as macrophage marker with r=0.31. The angiogenesis intensity showed significant differences (p<0.05) with the highest was in pulp polyp (12.00) followed by fibroma (11.81) and gingival polyp (9.67), however there was no significant difference between non neoplastic lesion (pulp polyp) and neoplastic lesion (fibroma). The CD68+ expression showed no significant differences (p=0.102>0.05) with the highest was in fibroma (51.32±31.64%) followed by non neoplastic pulp polyp (45.82±15.94%) and gingival polyp (29.98±13.51%). This result was in accordance with the biological properties of lesions from the aspect of angiogenesis and macrophage intensity that can be used as parameter for determining the growth and prognosis of lesion.